2018
DOI: 10.3389/fphar.2017.00974
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Acute Psychedelic Experience Predicts Therapeutic Efficacy of Psilocybin for Treatment-Resistant Depression

Abstract: Introduction: It is a basic principle of the “psychedelic” treatment model that the quality of the acute experience mediates long-term improvements in mental health. In the present paper we sought to test this using data from a clinical trial assessing psilocybin for treatment-resistant depression (TRD). In line with previous reports, we hypothesized that the occurrence and magnitude of Oceanic Boundlessness (OBN) (sharing features with mystical-type experience) and Dread of Ego Dissolution (DED) (similar to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
624
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 564 publications
(653 citation statements)
references
References 77 publications
(127 reference statements)
21
624
1
7
Order By: Relevance
“…Interestingly, the mPFC/ACC is strongly implicated in self-referential processing as well as mentalizing about others (D'Argembeau et al, 2007;Dixon, Thiruchselvam, Todd, & Christoff, 2017). This association between hierarchical position and ego-dissolution is particularly noteworthy given past findings that ego-dissolution and related mystical-type phenomena are key mediators of positive outcomes in psychedelic treatment paradigms (Belser et al, 2017;Johnson et al, 2019;Roseman, Nutt, & Carhart-Harris, 2018;Watts, Day, Krzanowski, Nutt, & Carhart-Harris, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, the mPFC/ACC is strongly implicated in self-referential processing as well as mentalizing about others (D'Argembeau et al, 2007;Dixon, Thiruchselvam, Todd, & Christoff, 2017). This association between hierarchical position and ego-dissolution is particularly noteworthy given past findings that ego-dissolution and related mystical-type phenomena are key mediators of positive outcomes in psychedelic treatment paradigms (Belser et al, 2017;Johnson et al, 2019;Roseman, Nutt, & Carhart-Harris, 2018;Watts, Day, Krzanowski, Nutt, & Carhart-Harris, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Recent work has consistently shown that the occurrence of mystical-type experiences is predictive of long-term therapeutic benefit from psychedelics (Maclean et al, 2011; Garcia-Romeu et al, 2014; Griffiths et al, 2016; Carhart-Harris et al, 2017, 2018; Roseman et al, 2018) and similar mechanisms may be at play in relation to improved mental well-being post NDE (Moody, 1975; Noyes, 1980; Ring, 1980; Groth-Marnat and Summers, 1998). It is pertinent to ask therefore, what common features shared between these states may be responsible for mediating the apparent long-term psychological benefits that follow them.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials have demonstrated potent and enduring antidepressive and anxiolytic effects of classical psychedelic drugs psilocybin and LSD Carhart-Harris et al 2016;Horstmann et al 2010;Ross et al 2016;Griffiths et al 2016;Grob et al 2011). Several studies have highlighted the mystical nature of the subjective experience resulting from administration of high dose psilocybin or LSD as a mediator for the psychiatric therapeutic benefits (Russ et al 2019;Garcia-Romeu et al 2014;Roseman et al 2018;Haijen et al 2018). However, recent evidence of sustained antidepressant-like effects of psilocybin in an animal rodent model for the study of depression after only a single dose suggests that solely biological mechanisms dependent on 5-HT 2A receptor activation may effectively underlie key CNS effects observed for this class of drug (Hibicke et al 2019).…”
Section: Introductionmentioning
confidence: 99%